Pock Formation of Streptomycetes endus with Production of Phage Taillike Particles - Ogata, Seiya (1982)
Plate (or slope) cultures of endomycin-producing Streptomyces endus (KCC S-0213) showed spontaneously developing pocks which increased in number during subculturing. Neither spore formation nor typical aerial hyphae formation was observed in the pocks, whereas formation of substrate hyphase was not inhibited. Almost all of the hyphae were broken or lysed in the pocks, and many phage tail tiplike particles were observed in the pocks. No self-replication activity was associated with the particles. The particles often formed a hexagonal crystal or a large crystal mass. The production of these particles did not occur in the liquid culture or in young or normal plate cultures having no pocks. These results were similar to those obtained from the plaque-making phenomenon, except for active phage production, in thiostrepton-producing Streptomyces azureus (ATCC 14921), which has been described previously.